The effectiveness of construction project briefing as an interpersonal communication process - Bowen, Paul; Cattell, Keith; Michell, Kathy; Kabayadondo, Elby (University of the Free State, 2006)
Englis: The main purpose of construction project briefing is to effectively transform the needs of the client from an abstract form into a concrete form. Research indicates a clear link between effective briefing and client satisfaction with their resultant buildings. This article documents the findings of a study concerning the effectiveness of construction project briefing as an interpersonal communication process. A case study approach was adopted. The sample included clients, building users, architects, quantity surveyors and project managers. The main finding was that there are no methodical procedures in place in the early stages of briefing. Conceptually, the various project participants were found to have a generic understanding of what ought to be included or excluded from briefing and debriefing, but there appears to be significant gaps between theory and practice.

Die hoofdoel van konstruksieprojek-voorligting is om die kliënt se behoeftes vanuit abstraktheid tot in ’n werklike struktuur doeltreffend te omskep. Dat kliënte as gevolg van behoorlike meedeling van projekopdragte wel met hul voltooide geboue tevrede gestel word, is deur navorsing bewys. Hierdie artikel bied die bevindinge voortvloeiend uit ’n gevallestudie oor die doeltreffendheid van konstruksieprojek-voorligting as interpersoonlike kommunikasieproses, aan. Die steekproef het kliënte, verbruikers van geboue, argitekte, bourekenaars en projekbestuurders ingesluit. Die hoofbevinding is dat tydens vroeë voorligtingstadia, word geen stelselmatige prosedures toegepas nie. Begripsgewys, dra die verskeie deelnemers algemene kennis van faktore wat tydens projekvoorligting en -evaluering in- of uitgesluit behoort te word, maar blykbaar bestaan daar aansienlike leemtes tussen teorie en die praktiese toepassing daarvan
Keywords: Briefing; Interpersonal communication; Client; Design; Construction project